Addiction recovery stories: Jerome Carson in conversation with Lisa Ogilvie. Issue 2 (30th December 2021) - Carson, Jerome; Ogilvie, Lisa
Abstract : Purpose: The purpose of this paper is to explore the accomplishments of those who realise addiction recovery. To the best of the authors' knowledge, this is the first in a series of recovery stories, where candid accounts of addiction and recovery are examined. In doing so, shared components of recovery are considered, along with the change and growth necessary to facilitate it. Design/methodology/approach: The CHIME (Connectedness, Hope, Identity, Meaning and Empowerment) framework comprises five elements important to recovery. It provides a standard to qualitatively study mental health recovery, having also been applied to addiction recovery. In this paper, an additional element for Growth has been introduced to the model (G-CHIME), to consider both recovery and sustained recovery. A first-hand account of addiction recovery is presented, followed by a semi-structured e-interview with the author of the account. This is structured on the G-CHIME model. Findings: This paper shows that successful and sustained recovery from alcohol addiction can be effectively explained using the G-CHIME model. Each element was well represented in the described process of reaching recovery. Originality/value: Each account of recovery in this series is unique, and as yet, untold.